Immune Checkpoints as Therapeutic Targets in Autoimmunity - Paluch, Christopher; Santos, Ana Mafalda; Anzilotti, Consuelo; Cornall, Richard J.; Davis, Simon J. (Frontiers in Immunology, 2018)
Antibodies that block the immune checkpoint receptors PD1 and CTLA4 have revolutionised the treatment of melanoma and several other cancers, but in the process, a new class of drug side effect has emerged - immune related adverse events. The observation that therapeutic blockade of these inhibitory receptors is sufficient to break self-tolerance, highlights their crucial role in the physiological modulation of immune responses. Here, we discuss the rationale for targeting immune checkpoint receptors with agonistic agents in autoimmunity, to restore tolerance when it is lost. We review progress that has been made to date, using Fc-fusion proteins, monoclonal antibodies or other novel constructs to induce immunosuppressive signalling through these pathways. Finally, we explore potential mechanisms by which these receptors trigger and modulate immune cell function, and how understanding these processes might shape the design of more effective therapeutic agents in future.